2017
DOI: 10.1097/prs.0000000000003241
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer and Reconstruction: Normative Data for Interpreting the BREAST-Q

Abstract: Background The BREAST-Q is a patient-reported outcome instrument used to evaluate outcomes in patients undergoing breast cancer surgery and reconstruction. Normative values for the BREAST-Q breast cancer modules have not been established, limiting data interpretation. Methods Participants were recruited via the Army of Women, an online community of women (with and without breast cancer), to complete mastectomy, breast conserving therapy (BCT), and reconstruction pre-operative BREAST-Q scales. Inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
71
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(90 citation statements)
references
References 34 publications
15
71
4
Order By: Relevance
“…At the 12mFU no difference was detected. These findings are in line with results of a study to gain normative data concerning the Breast-Q on 1201 women without prior history of breast cancer or breast surgery; women with a BMI30 kg/m 2 had lower Breast-Q scores for "satisfaction with breasts", "psychosocial well-being", "sexual well-being", and "physical well-being chest" compared to women with BMI<30 kg/m 2 [20]. Regarding the follow-up after BR, a study by Teo et al [31] also did not find an influence of the BMI on any Breast-Q scale.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…At the 12mFU no difference was detected. These findings are in line with results of a study to gain normative data concerning the Breast-Q on 1201 women without prior history of breast cancer or breast surgery; women with a BMI30 kg/m 2 had lower Breast-Q scores for "satisfaction with breasts", "psychosocial well-being", "sexual well-being", and "physical well-being chest" compared to women with BMI<30 kg/m 2 [20]. Regarding the follow-up after BR, a study by Teo et al [31] also did not find an influence of the BMI on any Breast-Q scale.…”
Section: Discussionsupporting
confidence: 85%
“…The latter was also true for patients 40 years, while these patients showed higher scores for "satisfaction with breasts" and "sexual well-being", respectively. Mundy et al [20] showed that patients >40 years had higher baseline scores for "psychosocial well-being", "sexual well-being" and "physical well-being chest". This finding could be confirmed by the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is rigorously developed, validated, specific to breast surgery and available in several languages. [64][65][66] Despite there being no universally accepted approach for determining the clinical significance of health-related QoL data, first estimates on minimally important differences for the BREAST-Q scores have now been published and these allow sample size calculations for clinical trials. 67 Clinical indicators of risk in OPS are likely to focus on factors such as rates of complications and return to the operating room as well as delays to start of adjuvant treatments or return to work.…”
Section: Discussionmentioning
confidence: 99%
“…Breast reconstruction following mastectomy has been shown to improve the quality of life as well as the social and psychological satisfaction of female patients undergoing mastectomy [1,2,3,4] Several options exist to reconstruct the breast such as autologous, implant-based reconstruction or a combination of both [5,6]. Implant-based breast reconstruction (IBR) remains the most common reconstructive approach in the United States and worldwide among women undergoing mastectomy [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%